2008
DOI: 10.1080/09670260701783730
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships among the MediterraneanAlexandrium(Dinophyceae) species based on sequences of 5.8S gene and Internal Transcript Spacers of the rRNA operon

Abstract: A phylogenetic analysis of the genus Alexandrium, including both the most common and rare species from coastal areas of the Mediterranean Sea was carried out. Nucleotide sequences of 5.8 S gene and Internal Transcribed Spacer regions of the rRNA operon were examined and analysed together with isolates of Alexandrium spp. from elsewhere in the world. These rDNA ribosomal markers were useful in delineating the phylogenetic position of species in the genus, as well as in determining relationships among isolates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 55 publications
(91 reference statements)
7
67
1
5
Order By: Relevance
“…Furthermore, the A. catenella cluster contains some A. tamarense morphotypes from China. The phylogenic grouping of isolates in this complex is consistent with the ribotype clades but not with the morphospecies that form the complex (37). They are in accordance with the recently developed trends (27, 37, 52) which question the phylogenetic, proteomic, biological, and morphological species definition for the A. tamarense complex.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Furthermore, the A. catenella cluster contains some A. tamarense morphotypes from China. The phylogenic grouping of isolates in this complex is consistent with the ribotype clades but not with the morphospecies that form the complex (37). They are in accordance with the recently developed trends (27, 37, 52) which question the phylogenetic, proteomic, biological, and morphological species definition for the A. tamarense complex.…”
Section: Discussionsupporting
confidence: 66%
“…Until now, differentiation among Alexandrium lineages has been investigated mainly by using ribosomal sequences (18,37,38,(43)(44)(45)(46). These analyses showed that the Alexandrium lineages are notably related to their geographic origins, and the lineages are defined as the North American, Western European, Mediterranean, Temperate Asian, Tropical Asian, and Tasmanian ribotypes.…”
Section: Discussionmentioning
confidence: 99%
“…PCR conditions were as follows: an initial denaturation at 95 8C for 10 min, 35 cycles of 30 s at 95 8C, 30 s at 52-56 8C, and 90 s at 72 8C and a final extension step of 7 min at 72 8C. PCR amplifications of 5.8S-ITS and LSU (D1/D2 domains) ribosomal genes has been reported in Penna et al (2008) and Fraga et al (2008), respectively. All PCR amplified products were purified using DNeasy gel extraction Kit (Qiagen, Valencia, CA, USA), and the products were directly sequenced (Eurofins MWG Operon, Ebersberg, Germany).…”
Section: Amplification and Sequencing Of Mitochondrial And Ribosomal mentioning
confidence: 99%
“…The posterior sulcal plate (s.p) is wider than long ( Figure 1D) 27,28]. Other than Malaysia, Alexandrium andersonii was also been found in the Irish coastal waters [27], Gulf of Naples, Italy [29], Aegean Sea, Greece [26,30] and along the coast of China [31]. …”
Section: Morphology Characterization Of Alexandrium Andersoniimentioning
confidence: 99%